Approximation of stochastic petri nets by means of continuous petri nets: adaptive approach - Benaya, Nabil; El Akchioui, Nabil; Mourabit, Taoufik (International Journal of Engineering and Technology, 2019)
Reliability analysis is often based on stochastic discrete event models like Markov models or stochastic Petri nets. For complex dynamical systems with numerous components, analytical expressions of the steady state are tedious to work out because of the combinatory explosion with discrete models. The contribution of this paper is to estimate the asymptotic comportement of stochastic nets by mean of continuous Petri nets according to a no linear modification of the maximal firing speed.